Biometric study of alpine populations of Apis mellifera L. (Bollettino di zoologia agraria e bachicoltura, 2024)
Samples of populations of Apis mellifera L. gathered in 5 6 localities distributed along the entire are of the Alps where, according to literature, the subspecies A.m. mellifera L., A.m. ligustica Spinola e A.m. carnica Pollmann would be established, were analysed and compared. On each of the individuals constituting the samples several measurements have been made and later elaborated according to biometric schemes. The following conclusions ha ve been drawn. There is a high degree of variability within and among the samples, which witnesses in favour of hybridizations occurred among the populations of the original subspecies, of which, however, traces stili remain as can be seen considering the graphics referring to each measured character. In our turn, in fact, we have spotted a few less variable samples, with attributes which are better fixed in the genetic patrimony. Finally, a high and to this day unknown correlation has emerged for the couple of characters tibia length-metatarsus width of the third pair of legs, which therefore appears to be particularly worthy of consideration in biometry programs on populations of A. mellifera.